On the Era of Yazdegard III and the Cycles of the Iranian Solar Calendar - Cristoforetti, Simone (Annali di Ca’ Foscari: Serie Orientale, 2014)
The well-known Persian solar era (Yazdegardī era) presents some problems. It is believed to have started with the official rise to the throne of the last Sasanian sovereign Yazdegard III in 632 CE and it is characterized by the one-day backward motion of all dates of the relative calendar every four Julian years. Are here analyzed some arabic and persian sources of the Islamic age in order to establish the kind of cycle or cycles that the Iranian solar calendar was based upon. in this regard, it is here observed that, following the statement of an outstanding figure of astronomer of the 10th century CE, the first year of the Yazdegardī era should have fallen on the third year of a four-yearly cycle of one-day backward motion of that calendar, and not in the first one, as is taken for granted in the available conversion tables.